1993
DOI: 10.1017/s1047951100001815
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral cellular response to profound hypothermia

Abstract: In our first two experiments, we examined brain tissue pH and tensions of oxygen and carbon dioxide in dogs core cooled to 20°C. So as to evaluate the effects of 60 minutes of circulatory arrest, 120 minutes of low-flow perfusion (25 mI/kg/mm), and 120 minutes of moderate-flow perfusion (50 mi/kg/mm), all conducted with and without pulsatile assistance. We further determined the effects of blood gas strategy on the same variables with 60 minutes of circulatory arrest. In a third experiment, we directly observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…19 In a separate study, pulsatile perfusion following 60 min of DHCA at cerebral perfusion pressure of 40 mmHg improved cerebral blood flow, cerebral metabolism, cerebral oxygen delivery, and cerebral vascular resistance compared to the nonpulsatile perfusion in piglets. 13,20 Watanabe and Washio 21 have documented that cerebral cellular injury may be induced by as little as 30 min of DHCA, and that pulsatile flow improved acidosis in the brain tissue at different flow rates compared to the nonpulsatile flow. Watanabe et al 22 have shown that brain tissue pH, oxygen tension, and carbon dioxide tension were better maintained in the pulsatile group than in the nonpulsatile group.…”
Section: Discussionmentioning
confidence: 99%
“…19 In a separate study, pulsatile perfusion following 60 min of DHCA at cerebral perfusion pressure of 40 mmHg improved cerebral blood flow, cerebral metabolism, cerebral oxygen delivery, and cerebral vascular resistance compared to the nonpulsatile perfusion in piglets. 13,20 Watanabe and Washio 21 have documented that cerebral cellular injury may be induced by as little as 30 min of DHCA, and that pulsatile flow improved acidosis in the brain tissue at different flow rates compared to the nonpulsatile flow. Watanabe et al 22 have shown that brain tissue pH, oxygen tension, and carbon dioxide tension were better maintained in the pulsatile group than in the nonpulsatile group.…”
Section: Discussionmentioning
confidence: 99%
“…They define topics deserving of further investigation. An article by Jobes et al 17 will summarize specific issues relating to coagulation in the young patient, and research by Ekroth et al 18 and by Wantanabe et al 19 will complete topics relating to cerebral protection by focusing on pulsatile perfusion and on strategies for rewarming respectively. The series will be concluded by a review by Auten 20 summarizing the characteristics in maturation of organs which distinguish the young from the older patient-changes which potentially influence the management of cardiopulmonary bypass.…”
mentioning
confidence: 99%